Influence of Lactobacillus buchneri as silage additive and forage: concentrate ratio on the growth performance, fatty acid profile in longissimus muscle, and meat quality of beef cattle - Rabelo, C. H. S. [UNESP]; Basso, F. C. [UNESP]; McAllister, T. A.; Lage, J. F. [UNESP]; Goncalves, G. S. [UNESP]; Lara, E. C. [UNESP]; Oliveira, A. A. [UNESP]; Berchielli, T. T. [UNESP]; Reis, R. A. [UNESP] (Canadian Science Publishing, Nrc Research Press, 2016)
Our objective was to investigate Lactobacillus buchneri as a silage additive and the forage: concentrate (F:C) ratio on growth performance and meat quality of finishing beef cattle. The trial was a 2 (corn silage untreated or inoculated with L. buchneri) x 2 (two F: C ratios, 60: 40 or 40: 60) factorial. Bulls fed a 40: 60 F: C diet containing inoculated silage had greater dry matter (DM) intake (P < 0.01) and average daily gain (P = 0.029) compared with other treatments. DM (P = 0.02) and neutral detergent digestibility (P < 0.01) were depressed by inoculation of corn silage with L. buchneri. Thiobarbituric acid concentration in meat increased (P < 0.01) by 15% in bulls fed the 60: 40 F: C diet compared with the 40: 60 F: C diet. Inoculation of silage increased (P = 0.02) the ratio of unsaturated fatty acids to saturated fatty acids. Compared with the 60: 40 F:C diet, the concentrations of polyunsaturated fatty acids (P = 0.03) and omega-6 fatty acids (P = 0.02) increased in longissimus muscle by 23% and 26%, respectively, in bulls fed the 40:60 F:C diet. Inoculation of corn silage with L. buchneri inconsistently improved the growth performance and meat traits of finishing bulls consuming diets differing in F:C.
Keywords: corn silage; digestibility; fatty acid profile; Lactobacillus buchneri; ruminal fermentation